China's state-owned banks' lending practices, 1994-2005: Empirical tests and policy implications - Richard C. K. Burdekin; Ran Tao (The Open Economics Journal, 2008)
More than half of the assets in China's banking system are accounted for by four huge state-owned commercial banks. This paper examines the changing factors influencing these banks' lending behavior over the post-1994 period on a province-by-province basis. Determinants include the concentration of state-owned enterprises, the level of provincial prosperity, deposit levels, and macroeconomic control variables. We confirm a downward trend in the banks' loan-todeposit ratio combined with some (mixed) evidence of more lending to richer provinces over time. SOE lending remained important for at least one of the four banks.
Keywords: 330; Chinese banks; lending; state-owned enterprises; provincial income; privatization; World Trade Organization